2019
DOI: 10.1002/jcb.29222
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification of a competing endogenous RNA network in cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is the second widespread liver tumor with relatively poor survival. Increasing evidence in recent studies showed long noncoding RNAs (lncRNAs) exert a crucial impact on the development and progression of CCA based on the mechanism of competing endogenous RNAs (ceRNAs). However, functional roles and regulatory mechanisms of lncRNA‐regulated ceRNA in CCA, are only partially understood. The expression profile of messenger RNAs (mRNAs), lncRNAs, and microRNAs (miRNAs) downloaded from The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…1C). Previous transcriptomesequencing studies also indicated that LINC00665 was overexpressed in tumor tissues of CCA patients 13,14,23 , Fig. 1 LINC00665 is upregulated and associated with poor prognosis and chemoresistance in CCA patients.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…1C). Previous transcriptomesequencing studies also indicated that LINC00665 was overexpressed in tumor tissues of CCA patients 13,14,23 , Fig. 1 LINC00665 is upregulated and associated with poor prognosis and chemoresistance in CCA patients.…”
Section: Resultsmentioning
confidence: 80%
“…1C ). Previous transcriptome-sequencing studies also indicated that LINC00665 was overexpressed in tumor tissues of CCA patients 13 , 14 , 23 , thus we further checked the expression of LINC00665 in 100 pairs of CCA samples and matched adjacent-normal tissues collected from Henan Provincial People’s Hospital. Our results revealed that LINC00665 was significantly upregulated in CCA patients, corresponding with previous results (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…lncRNAs function as competing endogenous RNAs (ceRNAs), which interrupt miRNA functions and alter protein expression, and this may be a characteristic hallmark in CCA. Genome-wide data analysis or RNA-Seq profiling identified various lncRNAs and ceRNA networks associated with CCA, and some candidate lncRNAs are significantly associated with survival rates (40)(41)(42). Recent studies have identified a number of lncRNAs that are associated with CCA progression and invasion.…”
Section: Cholangiocarcinoma Lncrnas As Competing Endogenous Rnas In Ccamentioning
confidence: 99%
“…We found that NNT-AS1 is mainly located in the cytoplasm of T24 and TCC-SUP cells ( Figure 3A). Growing evidence suggests that cytoplasmic lncRNAs can function as ceRNAs by competitively interacting with specific miRNAs [43][44][45]. A bioinformatic algorithm, starBase 3.0, was executed to search for a potential miRNA target of NNT-AS1.…”
Section: Nnt-as1 Acts As a Competing Endogenous Rna (Cerna) On Mir-49mentioning
confidence: 99%